Corrosion Inhibition Of Aquilaria Methanolic Leaf Extracts For Mild Steel In Hydrochloric Acid Solution - Lee, Helen Yun Sin (2018)
Corrosion is a problem that negatively affects many industries and causes these industries monetary losses. Many synthetic inhibitors were developed to overcome the corrosion problem. However, these synthetic inhibitors are harmful to human and the environment. In this study, the methanolic leaf extracts of Aquilaria malaccensis (noninoculated) and Aquilaria subintegra (non-inoculated, chemical inoculated, physical inoculated) leaf were investigated as green and sustainable corrosion inhibitors for mild steel in 1 M HCl solution.